2022
DOI: 10.1192/bjo.2022.45
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of family caregiving burden of persons with schizophrenia with and without transition of primary caregivers from 1994 to 2015 in rural China

Abstract: Background Little is known about how sociodemographic and clinical factors affect the caregiving burden of persons with schizophrenia (PwSs) with transition in primary caregivers. Aims This study aimed to examine the predictive effects of sociodemographic and clinical factors on the caregiving burden of PwSs with and without caregiver transition from 1994 to 2015 in rural China. Method Using panel data, 206 dyads of PwSs and their primary caregivers were investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…The participants in our study expressed emotions towards coping, such as resignation-acceptance, which were also reported by Olwit et al (2015) and Peng et al (2022) in a recently published study carried out in rural China. In addition, and congruent with previous research on caregivers of people with chronic mental disorders and other chronic conditions such as dementia and cancer, positive emotions, namely calm, hope, peace, control-strength and satisfaction were also identified in this study by ten caregivers (Balducci et al, 2008;Weimand et al, 2013;Olwit et al, 2015;Leow & Chan, 2017;Shiraishi & Reilly, 2019;Liu and Zhang, 2020;Peng et al, 2022). In our study, most family caregivers reported that they had experienced a turning point when they sought support from health professionals or family or when their relative X: Perceived mental health problems experienced in the past.…”
Section: Discussionsupporting
confidence: 86%
“…The participants in our study expressed emotions towards coping, such as resignation-acceptance, which were also reported by Olwit et al (2015) and Peng et al (2022) in a recently published study carried out in rural China. In addition, and congruent with previous research on caregivers of people with chronic mental disorders and other chronic conditions such as dementia and cancer, positive emotions, namely calm, hope, peace, control-strength and satisfaction were also identified in this study by ten caregivers (Balducci et al, 2008;Weimand et al, 2013;Olwit et al, 2015;Leow & Chan, 2017;Shiraishi & Reilly, 2019;Liu and Zhang, 2020;Peng et al, 2022). In our study, most family caregivers reported that they had experienced a turning point when they sought support from health professionals or family or when their relative X: Perceived mental health problems experienced in the past.…”
Section: Discussionsupporting
confidence: 86%
“…The family feel the burden of care costs due to the length of recovery at the health service and the frequency of recurrence, resulting in shorter re-admissions. The findings suggest that low income, stigma, and quality of family care are critical determinants of health-related quality of life, so efforts to increase life satisfaction focus on reducing stigma, increasing family income and strengthening the quality of family-centered care [21], [26].…”
Section: Discusion 41 the Burden Of Family Carementioning
confidence: 99%
“…Considering these undesirable consequences, serval studies tried to understand predictors of family caregiving burden for individuals living with schizophrenia 14 . Researchers found that some disease-related factors including patients' higher level of disability 15,16 , longer duration of illness 17 , more aggressive behaviors 18 were associated higher level of family caregiving burden. In addition, some caregiver-related factors such as low social support 19 , perceived stigma 20 were associated higher level of caregiver burden.…”
Section: Introductionmentioning
confidence: 99%